2017
DOI: 10.3892/mmr.2017.8009
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of anisodamine against myocardial ischemia/reperfusion injury through the inhibition of oxidative stress, inflammation and apoptosis

Abstract: The aim of the present study was to investigate the cardioprotective effects of anisodamine against myocardial ischemia/reperfusion (I/R) injury and the molecular mechanisms involved. The present results demonstrated that anisodamine attenuated myocardial infarct sizes, decreased the levels of creatine kinase and lactate dehydrogenase, whereas it increased the left ventricular (LV) systolic pressure, the LV end‑diastolic pressure, and the LV pressure maximum rising and falling rates in a myocardial I/R rat mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The mice were randomly divided into four groups (n = 5): Control group, ANIdown-regulating the expression of caspase 3 and Bax. 10,12 In addition, the combination of ANI and neostigmine improved acute fatal crush syndrome by activating α 7 nicotine acetylcholine receptor (α 7nAChR)-dependent JAK2-STAT3 pathway. 27 Surprisingly, the anti-inflammatory effect of ANI was also found to be applicable to tumor progression in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mice were randomly divided into four groups (n = 5): Control group, ANIdown-regulating the expression of caspase 3 and Bax. 10,12 In addition, the combination of ANI and neostigmine improved acute fatal crush syndrome by activating α 7 nicotine acetylcholine receptor (α 7nAChR)-dependent JAK2-STAT3 pathway. 27 Surprisingly, the anti-inflammatory effect of ANI was also found to be applicable to tumor progression in this study.…”
Section: Discussionmentioning
confidence: 99%
“…9 ANI has also been reported to have a significant anti-inflammatory effect, which can alleviate the damage of kidney and heart by inhibiting the activation of inflammasomes and the expression of inflammatory factors. 10,11 Similarly, ANI showed an anti-apoptotic effect in myocardial ischemic injury. 12 However, the role of ANI in tumors has not been revealed.…”
Section: Introductionmentioning
confidence: 96%
“…Ischemia-reperfusion injury is accepted as one of the contributors to many cardiovascular diseases by bringing irreversible damage to the endothelium by inducing cell apoptosis and inflammation [ 15 ]. The inflammatory cytokines generated in vivo by ischemia-reperfusion injury would recruit immune cells, which would further participate in exacerbating blood vessel barrier dysfunction by direct inflammatory cell infiltration and promoting thrombosis by activating circulating platelets [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that myocardial cell damage is closely related to Oxidative Stress (OS) and inflammation [7]. OS refers to an unbalanced state caused by excessive oxidation of the body.…”
Section: Protective Mechanism Of Xinmailong Injection On Cardiomentioning
confidence: 99%